SHE WAS TRAPPED IN A MAN’S BODY: A CASE REPORT OF ADRENOCORTICAL CARCINOMA - Ramos, Ralph Jefferson; Arkoncel, Maria Luisa Cecilia; Dungca, Ryan Joe; Arkoncel, Francis Raymond (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Adrenocortical carcinoma is a rare malignancy with an annual incidence of 1-2 per million population. It most commonly presents as hirsutism, acne, and clitoral enlargement. This case report documents how the symptoms presented in the patient, how it was diagnosed and treated. CASE A 33-year-old female had amenorrhea for a year, accompanied by receeding hairline, mustache, hirsutism more on the hypogastric area and lower extremities, rightsided abdominal pain and deepening of the voice. She brought an ultrasound result with an impression of adrenal mass. Whole Abdominal CT scan revealed right adrenal mass with downward displacement of the ipsilateral kidney. DHEA-S and serum testosterone were elevated. She subsequently underwent laparoscopic adrenelectomy. Histopathology showed adrenocortical carcinoma with extracapsular invasion. On follow-up, repeat DHEA-S and serum testosterone levels were normal. Three months post-operation, the patient complained of amenorrhea for which she was referred to an obstetrician who confirmed her pregnancy. She eventually had an uneventful delivery. CONCLUSION Thorough history and physical examination are essential in the diagnosis. Appropriate imaging studies and laboratory work-up are the cornerstone in the diagnosis of androgensecreting adrenal tumors. The only curative treatment is surgical resection.